PERANAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN PETANI PADI SAWAH DI KELURAHAN TUATUKA KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Mutmainah Mutmainah; Leta R. Levis; Ignatius Sinu (Buletin Ilmiah Impas, 2021)
This research was carried out from August to October 2019. The aims of this study were 1) to find out the role of farmer groups in Tuatuka village, 2) to find out the income earning of rice farmer’s in Tuatuka Village, and 3) to find out the relationship between the role of farmer groups and the income of rice farmers. This research was conducted by survey method, the 97 respondents from 128 farmers were by Simple Random Sampling. Data were analyzed descriptively by using Likert Scale and Spearman correlation. The results were, 1) the role of the paddy farmer groups in study site an average score as was 3,7 or 74,7%, it means that the learning class included the good category. As a collaboration working has an average of 3,60 or 72,0%, it means that a collaboration working included the good category. After that a unit were of production has an average of 2,85 or 57,03%. It means that, were production unit was included the moderate category.2) the average income of rice farmers in study site 2018 was Rp.10.383.703,- the highest income was Rp.21.562.300, and the lowest Rp. 5.103.100. and average in 2019 was Rp.11.845.444,- the highest was Rp. 23.262.444, and the lowest Rp. 6.102.700. 3)there is no relationship between the role of farmer groups and the incease in income earning of rice farmers in the study site.